Mobile-Assisted Language Learning Applications to Boost Student Engagement, Self-Regulation, and Learning Outcomes in Digital Environments - Dedi Arianto; Mahfud Heru Fatoni; Olabode, Adeyinka Ayoola (Global Education : International Journal of Educational Sciences and Languages, 2025)
The rapid penetration of mobile devices among students has created significant opportunities to optimize mobile-assisted language learning (MALL) for enhancing language acquisition in digital environments. Despite its potential, the implementation of MALL often remains suboptimal due to technical limitations, lack of pedagogical planning, and insufficient integration of interactive features, which limits its effectiveness in supporting structured learning. This study aims to examine how MALL applications influence student engagement, self-regulation, and language learning outcomes, while addressing the gap between technological affordances and instructional practices. Employing a mixed-methods design, the research integrates quantitative surveys, learning analytics, and qualitative interviews with higher education students who regularly use mobile applications for language learning. The methodology includes pre- and post-surveys to measure changes in engagement and self-regulation, log data to track usage patterns, and interviews to capture students’ perceptions and experiences. The findings reveal that MALL significantly enhances engagement through increased active participation, higher attendance, longer study duration, and more frequent interaction with materials. At the same time, MALL improves self-regulation by strengthening skills in time management, goal setting, monitoring progress, and maintaining persistence, leading to greater learner autonomy. Moreover, students with stronger self-regulation capacities were found to utilize MALL features more effectively, resulting in measurable improvements in vocabulary, grammar, and communicative competence. The study concludes that MALL’s effectiveness lies not only in delivering learning content but also in fostering engagement and supporting self-regulated learning. These results highlight the need for pedagogical designs that integrate technological interactivity with scaffolding strategies to maximize the potential of MALL as a learner-centered and sustainable approach to language learning in the digital era.